THE AQUI NETWORK: SOIL MOISTURE SITES IN THE LES LANDES FOREST AND GRAVES VINEYARDS (BORDEAUX AQUITAINE REGION, FRANCE) - Wigneron, Jean-Pierre; Dayau, Sylvia; Kruszewski, Alain; Aluome, Christelle; Guillot-Ehret, Marie; Al-Yaari, Amen; Fan, Lei; Guven, Serhat; Chipeaux, Christophe; Moisy, Christophe; Guyon, Dominique; Loustau, Denis (IEEE, 2018)
INRA (National Institute of Agricultural Research) has set up the AQUI network in the Bordeaux-Aquitaine region (southwestern France) in the framework of the SMOS cal/val activities. This network includes sites of in situ measurements which have been equipped with sensors measuring soil moisture (SM) and temperature, at various depths, and the height of the groundwater table. Four sites were installed in the Les Landes forest, which is one of the largest coniferous forests in Europe, and one site was installed close to vineyard fields of the Bordeaux Graves region. First results of the evaluation of the SM data retrieved from the L-band SMOS and SMAP passive microwave radiometers over the AQUI network are presented. The AQUI network was included in ISMN (International Soil moisture Network) in 2018.
Keywords: Soil moisture; water table; Les Landes forest; Bordeaux vineyards; SMOS; SMAP; ISMN; RETRIEVAL; SURFACE; CAROLS; Engineering; Geology; Remote Sensing